USP22 Promotes NSCLC Tumorigenesis via MDMX Up-Regulation and Subsequent p53 Inhibition - Ding, Fangbao (Int J Mol Sci, 2014)
Increasing evidence suggests that ubiquitin-specific protease 22 (USP22) has great clinicopathologic significance in oncology. In this study, we investigated the role of USP22 in human NSCLC tumorigenesis along with the underlying mechanisms of action. First, we determined the expression of USP22 in human NSCLC, as well as normal tissues and cell lines. We then studied the effects of USP22 silencing by shRNA on NSCLC cell growth in vitro and tumorigenesis in vivo, along with the effect on the p53 pathway. We found that USP22 is overexpressed in human NSCLC tissues and cell lines. USP22 silencing by shRNA inhibits proliferation, induces apoptosis and arrests cells at the G0/G1 phases in NSCLC cells and curbs human NSCLC tumor growth in a mouse xenograft model. Additionally, USP22 silencing downregulates MDMX protein expression and activates the p53 pathway. Our co-immunoprecipitation analysis shows that USP22 interacts with MDMX in NSCLC cells. Furthermore, MDMX silencing leads to growth arrest and apoptosis in NSCLC cells, and over-expression of MDMX reverses the USP22 silencing-induced effects. Taken together, our results suggest that USP22 promotes NSCLC tumorigenesis in vitro and in vivo through MDMX upregulation and subsequent p53 inhibition. USP22 may represent a novel target for NSCLC treatment.